2021
DOI: 10.12688/wellcomeopenres.16735.1
|View full text |Cite
|
Sign up to set email alerts
|

From severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) to coronavirus disease 2019 (COVID-19): a systematic review of the quality and responsiveness of clinical management guidelines in outbreak settings

Abstract: Background: Clinical management guidelines (CMGs) can be useful tools to guide clinician’s decision making and enable consistent evidence-based high-quality care. Here, we assessed whether their objective quality has improved over time by considering CMGs for severe acute respiratory syndrome (SARS), Middle East respiratory syndrome (MERS) and from different timepoints for coronavirus disease 2019 (COVID-19). Methods: We performed a rapid literature review, quality assessment and focus group consultation. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…This may indicate inequity in inclusion of these populations in treatment trials [101]. This is in line with findings from systematic reviews of SARS, MERS and COVID-19 CMGs [33].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This may indicate inequity in inclusion of these populations in treatment trials [101]. This is in line with findings from systematic reviews of SARS, MERS and COVID-19 CMGs [33].…”
Section: Discussionsupporting
confidence: 75%
“…Guideline development frameworks recommend regular reviews and CMG updates, every three to 5 years [109]. For emerging infectious diseases, such as influenza and COVID-19 where the epidemiology and new evidence may change rapidly, guidelines need to be flexible and adaptive [33]. Moreover, it is important to not overlook the quality of the CMGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent survey of 76 clinicians from 27 countries conducted during the COVID-19 pandemic identified issues in the implementation of COVID-19 CMGs, including limited access to treatments and equipment and lack of guidance for at-risk populations and resource-constrained settings [1]. These findings are supported by a series of systematic evidence reviews of existing CMGs, for viral haemorrhagic fevers (VHFs), chikungunya, mpox and severe acute respiratory syndrome (SARS), which found similar issues regarding availability, inclusivity, quality, and applicability of CMGs [2][3][4][5][6], particularly in Low-and Middle-Income Countries (LMICs).…”
Section: Introductionmentioning
confidence: 90%
“…
Prior research highlighting the complexity of clinical management guidelines (CMG) implementation, has suggested that limited access to treatments and equipment [1] and substantial issues regarding availability, inclusivity, quality, and applicability [2][3][4][5][6] hinder the implementation of CMGs in Low-and Middle-Income Countries (LMICs). This in-depth case study of Uganda -coincidentally occurring during the 2022 Sudan Virus Disease outbreak -aimed to explore contextual and supplementary factors which hinder or facilitate CMG development and implementation.
…”
mentioning
confidence: 99%